2023
DOI: 10.1021/acs.jnatprod.2c00974
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Renieramycin M into Renieramycins T and S by Intramolecular Photoredox Reaction of 7-Methoxy-6-methyl-1,2,3,4-tetrahydroisoquinoline-5,8-dione Derivatives

Abstract: In connection with our studies of biologically active 1,2,3,4-tetrahydroisoquinoline marine natural products, we describe herein a useful intramolecular photoredox transformation of 7-methoxy-6-methyl-1,2,3,4-tetrahydroisoquinoline-5,8-dione tricyclic models into 5-hydroxy-tetrahydroisoquinol[1,3]dioxoles in excellent yields. We applied this methodology to the transformation of renieramycin M into renieramycins T and S and the transformation of saframycin A. The results of cytotoxicity studies are also present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…11d However, the method has not been employed for the synthesis of the pentacyclic intermediates of Et-743. 20 Interestingly, the photolysis of the pentacyclic methoxyquinone 32 (as well as the subsequent 36) proceeded much faster than that of the previous bicyclic substrates 11d,14a (10 min vs overnight) to generate the [1,3]dioxole phenol 33, which was oxidized with (PhSeO) 2 O to hydroxyl ketone 34. As an advanced intermediate in Zhang's Et-743 synthesis, 13b the spectroscopic and spectrometric data of 33 were in good accordance with their reported values (see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11d However, the method has not been employed for the synthesis of the pentacyclic intermediates of Et-743. 20 Interestingly, the photolysis of the pentacyclic methoxyquinone 32 (as well as the subsequent 36) proceeded much faster than that of the previous bicyclic substrates 11d,14a (10 min vs overnight) to generate the [1,3]dioxole phenol 33, which was oxidized with (PhSeO) 2 O to hydroxyl ketone 34. As an advanced intermediate in Zhang's Et-743 synthesis, 13b the spectroscopic and spectrometric data of 33 were in good accordance with their reported values (see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9,10 In addition, we previously reported an intramolecular photoredox reaction that proceeded via the fluorescent-light irradiation of a dichloromethane solution of methoxy p-quinone to form a 1,3-dioxole ring (Scheme 1, eq 1). 11 The photochemical reactions of these quinones are believed to be initiated by the Norrish type II 1,5-H abstraction of the proximate hydrogen by a photoexcited alkoxy radical, as reported by Edwards and Ho. 12 In this study, we developed a novel method to synthesize benzo[g]chromene 2a via the photochemical reaction of p-quinone as a substrate.…”
Section: ■ Introductionmentioning
confidence: 84%
“…In a pioneering example of benzo­[ g ]­chromene synthesis using a photochemical reaction, Naito et al reported that 2a could be obtained in 4% yield by irradiating an acetonitrile solution of 1 with a 100 W high-pressure mercury lamp as the light source (Scheme , eq 2) . In our previous photochemical reaction, we found that the presence of a methyl group adjacent to the methoxy group was essential to the photochemical reaction of the methoxy p -quinone (Scheme , eq 1) . The reaction was initiated by the 1,5-H abstraction of the alkoxy radical produced by the photoexcitation of p -quinone.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations